EVALUASI KINERJA DOSEN DITINJAU DARI PRESTASI BELAJAR MAHASISWA DI JURUSAN KEBIDANAN POLITEKNIK KESEHATAN KEMENTERIAN KESEHATAN KUPANG TAHUN 2013 - SERLYANSIE VICTORIA BOIMAU (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
This research ws the first of its type to be studied in the midwifery department of Politeknik Kesehatan Kementerian Kupang. Aim of this research was to evaluate college teachers’ performance in the insight of students’ achievement in the midwifery department of Politeknik Kesehatan Kementerian Kupang. This research undertook a descriptive study by employing both quantitative and qualitative approaches. Research population comprised college teachers and students in the midwifery department of Politeknik Kesehatan Kementerian Kupang. Research analysis employed a bivariate approach by Chi Square test and Crosstab relying on the contingency coefficient. Analysis result points human resources as .816, organizing as .504, finance as .491, curriculum as .879, andcompetency/qualification as .823. Conclusion points out a very strong relationship between human resources, a moderate relationship between organizing, a moderate relationship between finance, a very strong relationship between curriculums, and a very strong relationship between qualifications. Recommendation of this research is an enhancement of reliable and professional human resources, design systematic organizing, allocation of adequate financials, arrangement of curriculum based on given guidance, and to enhance quantity of teachers according to academic qualification (master degree) in the Midwifery Deparetement of Politeknik Kesehatan Kementerian Kupang.